NHERI education and community outreach: longitudinal, educational outcomes of a coordinated, distributed network - Nelson, Robin; Vielma, Karina I.; Browning, JoAnn (Frontiers in Built Environment, 2025)
The U.S. National Science Foundation (NSF) Natural Hazards Engineering Research Infrastructure (NHERI) Network Coordination Office (NCO) Education and Community Outreach (ECO) led coordinated efforts to promote educational activities along various pathways for students and educators targeted at broadening participation in and awareness of natural hazards engineering research through the Research Experiences for Undergraduates (REU) Summer Program, the Graduate Student Council (GSC), and the Summer Institute for Early Career Researchers and K-12 Educators. NHERI connects a diverse group of undergraduate and graduate students, faculty and K-12 educators, and researchers interested in mitigating the effects of natural hazards through these flagship educational programs. After 6 years of implementing these integrated educational activities, longitudinal outcomes and impacts for both students and faculty have been collected and are reported in this paper. Embedded in this report are several best practices used in educational outreach for recruitment, mentoring, and engagement of diverse participants that have been evaluated and enhanced through assessment and in collaboration with the larger NHERI network. Throughout 6 years of leading education activities, these practices have also helped create an intentional focus on challenge areas and informed the evolution of interdisciplinary pathways for natural hazards engineering research.